Batasan dan Pembuktian Perzinaan dalam Hukum Islam dan UU No. 1 Tahun 2023: Perspektif Kriminologi - Gede Henry Suardita; Muhammad Irayadi (Decisio: Jurnal Ilmiah Hukum, 2025)
This study examines the definition and proof of adultery in Islamic law and Law No. 1 of 2023 from a criminological perspective. It highlights the differences in how these legal frameworks address adultery and their impacts on society’s moral order. The research explores the criminal sanctions provided by Islamic law and compares them with the more lenient approach of the Indonesian legal system under the new criminal code. The study aims to offer a comprehensive analysis of the regulatory and normative aspects of adultery law and its practical implementation. This research employs a qualitative method with a normative legal approach, analyzing regulations and legal norms. Primary and secondary data are used, collected through literature studies, including official documents, legal books, journals, and previous research. The findings indicate that Islamic law’s strict sanctions serve as a strong deterrent against adultery, while Law No. 1 of 2023 adopts a more restorative approach, allowing victims to report offenses. Despite the differences, both legal systems aim to protect social order by upholding moral standards. The research suggests that balancing these legal approaches could help harmonize legal norms and improve their application in Indonesia.